Hedonic and utilitarian performances as determinants of mental health and pro-social behaviors among volunteer tourists - Han, Heesup; Meng, Bo; Chua, Bee Lia; Ryu, Bobby Hyungseo (Multidisciplinary Digital Publishing Institute, 2020)
International volunteer tourism is an emerging and sustainable trend of the global tourism industry. In this study, we attempted to provide a clear comprehension of volunteer tourists’ mental health increase and pro-social intention formation. A survey method and quantitative approach were used. Our result from the structural analysis showed that hedonic and utilitarian performances, mental health, and volunteer tourism engagement had significant associations and that these relationships contributed to improving pro-social intention. In addition, results from the metric invariance assessment revealed that the volunteer tourism engagement and pro-social intention relation was under the significant influence of problem awareness and ascribed responsibility. Mental health and engagement acted as significant mediators. The comparative importance of volunteer tourism engagement was uncovered. Overall, our results provided a sufficient understanding of volunteer tourists’ pro-social decision-making process and behaviors.